Remediation strategies for enhancing economic students' understanding and performance in South Africa - Nana Yaw Brenya Agyeman; Vanessa Aphane (Inovasi Kurikulum, 2026)
Economics is an important subject in South African schools because it equips learners with the knowledge to understand economic systems and address economic challenges. However, limited evidence explains how Economics teachers in under-resourced schools respond to learners' misconceptions through practical remediation strategies. This study aimed to explore the remediation strategies used by Economics teachers to address learners' misconceptions and support their understanding and academic performance. A qualitative case study approach was employed to examine teachers' experiences and instructional practices in under-resourced South African schools. Data were collected through semi-structured interviews with 20 purposively selected participants and analyzed thematically. The findings identified five core remediation strategies: active learning, real-world applications, collaborative learning, formative assessment, and approaches addressing socioeconomic challenges. Active learning and real-world applications supported learners in engaging with and contextualizing economic concepts, while collaborative learning facilitated peer interaction and shared understanding. Formative assessment enabled teachers to identify misconceptions and provide timely feedback, while attention to socioeconomic barriers highlighted the importance of learning resources and infrastructure. Technology integration also supported learners' engagement and understanding. These findings demonstrate that effective remediation requires context-sensitive instructional strategies, adequate resources, and institutional support.   Abstrak Ekonomi menjadi  mata pelajaran penting di sekolah Afrika Selatan karena anggotanya dididik dengan pengetahuan untuk memahami sistem ekonomi dan menghadapi berbagai tantangan ekonomi. Namun, bukti mengenai bagaimana guru ekonomi di sekolah dengan keterbatasan sumber daya menanggapi miskonsepsi peserta didik melalui strategi remediasi yang praktis masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi strategi remediasi yang digunakan guru ekonomi dalam mengatasi miskonsepsi serta mendukung pemahaman dan prestasi akademik peserta didik. Penelitian ini menggunakan pendekatan studi kasus kualitatif untuk mengkaji pengalaman dan praktik pembelajaran guru di sekolah Afrika Selatan yang memiliki keterbatasan sumber daya. Data dikumpulkan melalui wawancara semi-terstruktur terhadap 20 partisipan yang dipilih secara purposif, kemudian dianalisis menggunakan analisis tematik. Temuan mengidentifikasi lima strategi utama, yaitu pembelajaran aktif, penerapan konsep dalam konteks nyata, pembelajaran kolaboratif, asesmen formatif, dan pendekatan yang mempertimbangkan tantangan sosial ekonomi. Pembelajaran aktif dan konteks nyata mendukung interaksi serta pemahaman konsep ekonomi, sedangkan pembelajaran kolaboratif memfasilitasi interaksi dan pemaknaan bersama. Asesmen formatif membantu guru mengidentifikasi miskonsepsi dan memberikan umpan balik secara tepat waktu. Integrasi teknologi juga mendukung keterlibatan dan pemahaman peserta didik. Temuan menunjukkan bahwa remediasi yang efektif memerlukan strategi pembelajaran yang kontekstual, didukung oleh sumber daya dan dukungan institusional yang memadai. Kata Kunci: asesmen formatif; mata pelajaran ekonomi; remediasi strategis; tantangan sosial-ekonomi